Motivating Factors at the Career in Accounting and Finance : Analysis of Empirical Study - Nowak, Marta (Czynniki motywujące w karierze w rachunkowości i finansach : analiza studium empirycznego, 2010)
The paper covers the subject of motivation in accounting and finance. It is based on the author’s research which has been conducted on the group of accounting and finance students at the beginning of their career. The research reveals the intensity of different motivational factors which can be applied to people who work in accounting and finance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 132-143
Keywords: motivators; motivating factors; accounting; finance